Development of Innovation “tokotki.id” to Increase the Capacity of Household Financial Improvement Strategy of Indonesian Migrant Community in Malaysia - Yuli Agustina; Ita Prihartining Wilujeng; Afwan Hariri Prohimi (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
tokotki.id is an innovation aimed at enhancing the financial improvement strategies of Indonesian migrant households in Malaysia. The platform offers various services and products specifically designed to meet the needs of the Indonesian community seeking Malaysian products through the currently popular "Jasa Titip" (proxy shopping) service in the online business world. With its innovative approach, the presence of tokotki.id plays a role in addressing the financial challenges faced by the Indonesian migrant community in Malaysia. Through tokotki.id, migrants can easily and efficiently access various Malaysian products to sell in Indonesia. Additionally, the platform provides information and advice on personal financial management and tips for optimizing their income in Malaysia. Thus, tokotki.id helps migrants enhance their financial management capabilities through an online business model. Another feature that can be utilized from tokotki.id is the online marketplace, which allows migrants to sell local Indonesian products to the community in Malaysia. This creates new business opportunities for migrants to increase their income and diversify their sources of earnings. Furthermore, tokotki.id provides a platform for migrants to share experiences and tips about life in Malaysia, fostering a solid and supportive community. Indonesian migrants in Malaysia can improve their financial stability and family lives through innovations like tokotki.id, which provides access to products and financial services while enhancing users' financial management skills. This platform offers new opportunities for the migrant community to achieve financial independence and well-being.